Peripheral Dentinogenic Ghost Cell Tumor of the Alveolar Mucosa: A Rare Case Report: Peripheral Dentinogenic Ghost Cell Tumor - Mashhadi-Abbas, Fatemeh; Atarbashi-Moghadam, Saede; Khamoushi , Fatemeh zahra; Moradi , Yasaman; Hosseini Yazdi , Maryam (Journal of Dental School, 2025)
Objectives: Peripheral (extra-osseous) dentinogenic ghost cell tumors are an extremely rare type of odontogenic lesions. They show a slight male predilection and most commonly occur in the anterior gingiva of the mandible. The peak incidence is above 50 years of age, and unlike the intraosseous type, they are generally nonaggressive. Diagnosing intra-oral lesions can be challenging, and less common lesions are often overlooked. Case: This report aimed to describe a peripheral dentinogenic ghost cell tumor as a painless, pedunculated mass in a 62-year-old male. Conclusion: Understanding this unusual entity can facilitate a proper diagnosis and enhance our comprehension of its biological behavior.